Validação e aplicação da RT-QPCR de RNAm codificantes de citocinas em gatos naturalmente infectados pleo coronavírus felino (FCOV) - Zadra, Vívian Ferreira [UNESP] (2013)
The feline infectious peritonitis virus (FIPV) causes a fatal disease, and systemic immune mediated. The FIPV contains mutations of feline enteric coronavirus (FECoV) and antemortem diagnosis of FIP is challenging because most cats are positive for FCoV in serological and DNA amplification. The differentiation between infection the FIPV and FECoV is hard being conclusive post-mortem by histopathological examination. RT-PCR for detection of feline coronavirus mRNA in peripheral blood is a diagnostic test which shows the infection and replication of the virus. However, these tests can’t distinguish between strains producing FIP and FECoV. In the pathogenesis of infection, the infected cells induce an immune exacerbated production of cytokines. Thus, our goal was to determine whether cats with FIP express mRNA encoding cytokines altered form compared to healthy animals. Therefore, blood samples from 44 cats from catteries of SP and RJ were collected at 4 times within 4 months. From the total RNA, we performed RT-qPCR mRNA coding for feline cytokine (IL-1, IL-2, IL-6, IL-10, IL-12, TNF-α, IFN-γ) normalized by GAPDH. It was observed that, for the cytokines IL-1, IL-2, IL-6 and IL-10 high scores were obtained in most animals. However, IL-12, TNF-α and IFN-γ were increased only in some groups, which may be associated with FIPV infection. The animals with high values for these cytokines had clinical signs consistent with the disease and contact with animals that developed FIP